An Introduction and Critical Assessment of Smart City Developments - László Gere (DETUROPE)
The urban development methods in the 21st century focus more and more on the different kinds of IT solutions which are increasingly embedded in the operation of urban functions. Therefore, great attention has to be paid on them during the planning process. The so-called smart city solutions are of key importance from the cities’ social-economic development viewpoint, and together with their rapid spread, their scientific analysis is very important as well. This article deals with the growing importance of cities in the 21st century. Different factors affect this process. The first one is demographic change, the global increase of urban population. The second factor is the technological revolution, which significantly transforms the operation and understanding of our cities. The third one is the increasing economic role as well as the changing governance issues of cities. After introducing these background factors of the changing urban environment, the article focuses more on the smart city solutions. Firstly, it deals with the differences and uncertainties of its definition as well as the appearance of the related definitions. Secondly, it introduces the scientific discourse of the topic, to illustrate the most important differences, debates and arguments emerging in relation with the smart city developments. The last part of the article highlights the social development aspects of smart city developments, their role in decreasing social inequalities.